Kapitał zagraniczny a bezpośrednie inwestycje zagraniczne w ujęciu modelu Mundella-Fleminga - Tarasiński, Leszek (Foreign Capital and Foreign Direct Investment in the Mundell-Fleming's Model, 2007)
Foreign direct investment (EDI) is generally seen as an important factor of economic development with particularly great meaning for countries completing economic transformation. Individual countries, including Poland, are using all means to attract this sort of investment. Growing needs in this field are usually strictly related to "hunger" of knowledge about the effect of this investment both in current economic process and in structural changes of national economies. The main aim of this paper is to give some sort of an answer about possibility interpretation of the impact of FDI upon particular economic system by using widely known Mundell-Fleming's model of open economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 420-431